Analysis of the Online Learning Impact on the Students’ Self-Discipline Improvement - Mardiyah, Mutmainatul (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2024)
Student self-discipline does not emerge and develop suddenly without education, training, and internal and environmental encouragement. The research conducted in the Bachelor's Program of Public Health at MH. Thamrin University aims to analyze the online learning impact on the students’ self-discipline improvement. Quantitative research data were obtained by distributing questionnaires to twenty respondents as samples through Google Forms. The sampling was carried out randomly or through simple random sampling. The collected data were processed according to research procedures and analyzed using multiple linear regression analysis in SPSS 20. The results of this study indicate that self-discipline is crucial in online learning, and it can be fostered through various actions and measures such as motivation, scheduling, organizing, choosing a suitable study space, avoiding distractions, communication skills, time management, and contingency planning. These actions significantly contribute